The Role of Estrogen Receptor β (ERβ) in the Establishment of Hierarchical Social Relationships in Male Mice - Nakata, Mariko; Ågmo, Anders; Sagoshi, Shoko; Ogawa, Sonoko (Frontiers in Behavioral Neuroscience, 2018)
Acquisition of social dominance is important for social species including mice, for preferential access to foods and mates. Male mice establish social rank through agonistic behaviors, which are regulated by gonadal steroid hormone, testosterone, as its original form and aromatized form. It is well known that estrogen receptors (ERs), particularly ER α (ERα), mediate effects of aromatized testosterone, i.e., 17β-estradiol, but precise role played by ER β (ERβ) is still unclear. In the present study, we investigated effects of ERβ gene disruption on social rank establishment in male mice. Adult male ERβ knockout (βERKO) mice and their wild type (WT) littermates were paired based on genotype- and weight-matched manner and tested against each other repeatedly during 7 days experimental period. They underwent 4 trials of social interaction test in neutral cage (homogeneous set test) every other day. Along repeated trials, WT but not βERKO pairs showed a gradual increase of agonistic behaviors including aggression and tail rattling, and a gradual decrease of latency to social rank determination in tube test conducted after each trial of the social interaction test. Analysis of behavioral transition further suggested that WT winners in the tube test showed one-sided aggression during social interaction test suggesting WT pairs went through a process of social rank establishment. On the other hand, a dominant-subordinate relationship in βERKO pairs was not as apparent as that in WT pairs. Moreover, βERKO mice showed lower levels of aggressive behavior than WT mice in social interaction tests. These findings collectively suggest that ERβ may play a significant role in the establishment and maintenance of hierarchical social relationships among male mice.